Into the Hands of the Many: Production and Persistence in Rural Russia - Gambold, Liesl L. (Anthropologica, 2022)
In this paper, the Russian village of Moshkino pro? vides an opportunity to analyze neoliberal market development in the postsocialist context. Unenthusiastic growth in individual farming has resulted due to a desire among villagers to farm collectively. This desire is based on internalized and culturally accepted forms of labour exchange and social welfare. Villagers have succeeded in creating a neoliberal collective?a farm that operates under basic market principles but maintains the labour and social support structure of the traditional collective. The Russian model is a salient example of how capitalism cannot be exported as uniformly as consultants have suggested.